Minister Terawan encourages Usadha Bali development under Traditional Balinese Medicine branding - Ida Bagus Gede Karyambara Putra (Bali Tourism Board, 2020)
In Bali, Study of traditional herbal medicine is known under term Usadha, derived from Sanskrit word Ausadhi means healing plants. The ancient wisdom of botanical medicine texts has been compiled on Lontar (Dried-Borassus leaf) under name Lontar Usadha. Traditional Balinese Usadha treatment is carried out by a shaman called Balian; whether Balian Ketakson or Balian Usadha. Usadha practice on the island of Bali is strongly related to herbal plants' existence. Herbal medication has been proven in Bali as a primary treatment for the patient since ancient times. However, due to current medication service, people no longer prefer a botanical-based therapy as the first option. As a result, the number of herbal plants on the island of Bali has been plummeting over the years. Although on some occasions, the central government and provincial government had suggested cultivating herbaceous plant as a decorative plant on a household level, yet the program did not make any significant impact. In December 2019, Governor of Bali, Wayan Koster expressed his deep interest on indigenous health service industry to be provided by hospitals, both state and private. On occasion, Indonesia minister of Health, Terawan Agus Putranto, showed his support for the development of health tourism, travelling medicine, and complementary traditional services with local genius. They both agreed that the service would be promoted under 'Traditional Balinese Medicine (TBM) service' branding. In future, it is expected that TBM would be available as an alternative service on Bali hospitals. The facility would promote herbal industry development as well as herbal plant preservation through the availability of local herb farms to be established in ​​Bangli, Karangasem, and Tabanan areas.